2007
DOI: 10.1002/jmv.20781
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiological studies show that hepatitis A virus is endemic among active homosexual men in Europe

Abstract: Large outbreaks of hepatitis A have occurred in Denmark, Germany, the Netherlands, Norway, Spain, Sweden, and the United Kingdom during the period 1997-2005 affecting homosexual men. A collaborative study was undertaken between these countries to determine if the strains involved in these hepatitis A outbreaks were related genetically. The N-terminal region of VP1 and the VP1/P2A region of the strains were sequenced and compared. The majority of the strains found among homosexual men from the different Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 23 publications
0
47
0
2
Order By: Relevance
“…Other early studies identified oro-anal sexual contact as the most likely transmission route among MSM [10]. In recent years, outbreaks of hepatitis A among MSM have been described in most high-income countries [11].…”
Section: Hepatitis Amentioning
confidence: 99%
See 2 more Smart Citations
“…Other early studies identified oro-anal sexual contact as the most likely transmission route among MSM [10]. In recent years, outbreaks of hepatitis A among MSM have been described in most high-income countries [11].…”
Section: Hepatitis Amentioning
confidence: 99%
“…Recently, a collaborative European study was undertaken to determine if HAV strains that cause outbreaks among MSM in different countries are genetically related [11]. By comparing sequences, it was shown that the majority of strains found among MSM in the participating European countries formed closely related clusters belonging to genotype 1A.…”
Section: Hepatitis Amentioning
confidence: 99%
See 1 more Smart Citation
“…Presumptive positive samples were rerun using a nested classic RT-PCR using primers with slight modifications targeting the VP1-2A region (6,11). The sequences detected on the dates from the two companies showed similarity for 455 of 460 nucleotides, and were typed as a HAV genotype IA.…”
mentioning
confidence: 99%
“…With regard to adults, certain categories of people, such as men who have sexual intercourse with men, both injection and noninjection drug users, and travelers returning from developing countries, are exposed to a higher risk of infection and therefore are subjected to cyclic outbreaks of hepatitis A (1,3,8,11,12,15,17,18). It is also worth mentioning that HAVinfected persons with chronic liver disease are likely to develop fulminant hepatitis A (14, 16).…”
mentioning
confidence: 99%